PERAN DINAS PERINDUSTRIAN, KOPERASI DAN UMKM DALAM PEMBERDAYAAN UMKM SENTRA INDUSTRI KONVEKSI DI DESA PADURENAN KECAMATAN GEBOG KABUPATEN KUDUS - Nur, Ida; ., Purwoko (Journal of Politic and Government Studies, 2017)
Abstract: The role of the Office of Industry, Cooperatives and SMEs in SME Empowerment Centers Industrial Convection in the village Padurenan Subdistrict Gebog Kudus District. The presence of SMEs not only in order to increase revenue, but also to ensure equal distribution of income. This is understandable because the SME sector involves a lot of people with a variety of business cases. The government already has a commitment in terms of empowering the community economy is SMEs and cooperatives. Therefore, the role of government in providing a much-needed empowerment. This research was conducted by using a combination of qualitative research and quantitative descriptive qualitative approach remains as the main approach. The collection of data used in this study were interviews, observation, documentation and questionnaires (questionnaire). The results showed that the role of government represented by the Department of Industry, Cooperatives and SMEs Kudus District in empowerment has been successful but not maximum, can be seen still their supporting factors such as labor quite a lot and the support of the relevant parties, but there are also factors inhibiting as the low quality of human resources; limited access to marketing; limited capital. The government's role be optimized to empower the need to perform these steps: the government should increase financial capability to strengthen its capital; the government should develop a marketing order sales turnover has increased; governments need to develop human resources; the government should regulate the regulation and control strategies such as increased ease in licensing services and institutional strengthening. Keywords: Role of Government, Empowerment, Industrial Convection.